Foucaultian Discourse Analysis as a Research Methodological Tool. - Mauricio dos Santos Ferreira; Clarice Salete Traversini (Universidade Federal do Rio Grande do Sul, 2013)
Based on Michel Foucault's work, this paper aims at operating with the notion of discourse as a research methodological tool. We selected the Jobs & Opportunities section from Zero Hora newspaper published in 2008, to analyze how the professional profile desired by the contemporary work market has been constituted in order to support neoliberal discourses as truths. The study was initially carried out considering the notion of discourse in a kind of laboratory so as to understand its potentiality. Later, weanalyzed excerpts from newspapers by operating with one of the internal procedures of discourse - the author - regarded as a function that, ratherthan being an intellectual property, provides the text with coherence.